Left Heart Changes in Hypertensives Attending Rivers State University Teaching Hospital: An Echocardiographic Review - Ngozi CS; Deinma A; Rita W; Bonas H (Ibom Medical Journal)
Background: Hypertension, commonly known as high blood pressure, is a significant health challenge globally and in Nigeria, where it stands as the primary cause of cardiovascular diseases. Hypertensive heart disease refers to the complex and diverse change of the cardiac structure and function secondary to hypertension.